Evaluation of accelerated carbonation curing in cement-bonded balsa particleboard - Cabral, Matheus Roberto; Nakanishi, Erika Yukari; Santos, Valdemir dos; Gauss, Christian; Santos, Sergio Francisco dos [UNESP]; Fiorelli, Juliano (Springer, 2018)
This study aimed to assess the potential usage of balsa wood to produce cement-bonded particleboards as well as to study the effects of accelerated carbonation on the cement-bonded balsa particleboard. Particleboards were subjected to two different curing conditions, (1) conventional curing: control-curing for 48 h in a climatic chamber, followed by 25 days in a saturated environment (98 +/- 2%) in sealed plastic bags at 23 degrees C, (2) accelerated carbonation-curing for 48 h in a climatic chamber, and then in environment with CO2 (24 h concentration of 15%), followed by 24 days in a saturated environment (98 +/- 2%) in sealed plastic bags at 23 degrees C. After 28 days of curing, the particleboards degree of carbonation was evaluated by TG-DTG and XRD analysis. Thermal, physical and mechanical characterizations were conducted following the recommendations of ASTM-E1530 and DIN: 310, 322, 323 standards, respectively. Accelerated carbonation decreased the portlandite content and increased of calcium carbonate content of the studied particleboards. Thermal properties showed that the particleboards could be used as an insulation material in accordance to European Standard (BS EN 13986). Physical and mechanical properties of the studied materials showed that they are potential building particleboard, because this material satisfied the requirements of ISO 8335 standard.
Keywords: Accelerated carbonation; Forestry products; Wood; Portland cement; Cement composites